FACTORS INFLUENCING CONSUMER SATISFACTION WITH SOLAR WATER HEATERS - P. RADHA RANI, CH. BHAVYA PADMINI, V. VIJAYA LAKSHMI and (The Journal of Research, PJTSAU, 2017)
India is a sunny country with a solar energy potential of 20 mw every square km. At present, only a tiny fraction was being tapped. Solar energy can be used directly in two forms –producing heat or light. Production of light and electric current from the sun’s rays users‘ photovoltaic technology’, which involves direct conversion of sunlight into electricity. The thermal form of solar energy is used for cooking, water heating or purification, drying and fruit ripening, lighting, distillation or producing steam for power generation. Apart from cooking, heating water dominates the energy needs of households. For households in developing nations, heating water was often the most energy intensive process, and thereforethe most expensive or time-intensive. In communities throughout the developing world, poor households struggle to meet their hot water needs.